CT-based agile 3D printing system for pre-operative planning of orthopaedic surgeries. (16th March 2020) - Tran, Ton; Liu, Wencheng; Chen, Bernard K.; Molotnikov, Andrey; Wu, Xinhua; Pun, Jerome
Addressing the increase in complexity and number of orthopaedic surgeries especially in the aging population is a major challenge to orthopaedic surgeons. The availability of physical model of patient-specific bones can benefit pre-operative planning of surgeries and lead to better surgical options and improved outcomes. This paper describes a CT-based agile 3D printing system for manufacturing patient-specific bones that can be used for preoperative planning and assist in the choice and application of orthopaedic implants.